Identification of risk profiles among persons attending a sexually transmitted infection clinic in Estonia - Karolin Toompere; Krõõt Arbo; Ülo Maiväli; Made Laanpere; Maigi Eisen; Kirill Guskov; Anneli Uusküla (PLoS ONE, 2026)
Background While generalized STI prevention guidelines exist, individuals present with diverse interconnecting risk behaviors and needs. This cross-sectional study used latent class analysis to identify distinct behavioural profiles among men and women undergoing STI testing and to examine their potential implications for STI prevention. Methods Data was collected by questionnaire from 1171 individuals seeking STI testing at the North Estonia Medical Centre between August 2022 and October 2023. Latent class analysis was applied to identify subgroups based on eight relevant STI risk variables. Separate models were fitted to men and women. Results We propose three latent classes for both sexes. Among men, three classes were identified: “multiple partners; elevated behavioural risk” (62.4%); “predominantly monogamous; fewer behavioural risk indicators” (21.9%); and, “multiple partners; previous STI history; concentrated co-occurring risk” (15.7%). Women were categorised as follows: “new sexual partners; inconsistent condom use” (41.6%); “multiple partners; previous STI history; concentrated behavioural risk” (30.2%); and, “predominantly monogamous; possible partner-related exposure” (28.2%). The identified profiles demonstrated heterogeneity in sexual behaviour, condom use, prior STI history, and substance use across STI clinic attendees. Conclusions The identified behavioural profiles highlight how co-occurring risk factors cluster within STI clinic populations and may help contextualise prevention discussions alongside individualized clinical assessment. These findings may support prevention discussions addressing partner communication, condom use, substance use, IPV awareness, and partner notification.